EVALUASI SISTEM PROTEKSI PETIR INTERNAL PADA INSTALASI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) KALI JARI - Faishal, Luthfi Nur; Utomo, Teguh; Dhofir, Moch. (Jurnal Mahasiswa TEUB, 2024)
Evaluation of the Internal Lightning Protection System in Micro Hydro Power Plants (MHPP) needs to be carried out to support the continuity of generator work so that the supply of electrical energy is not interrupted. The evaluation carried out included the internal lightning protection system and the existing grounding system at the Kali Jari PLTMH. Based on the lightning protection level of the SNI 03-7015-2004 standard, an efficiency value of 36.47% is obtained at protection level IV with an efficiency value of 0-80%. To obtain the rated value of an arrester for an internal lightning protection system, it is necessary to know the value of the induced voltage that occurs in the network where the distribution lines are open enough to be exposed to indirect strikes. Using calculations from the simplified Rusck method, it was concluded that the change in the value of the induced voltage due to a lightning strike to the distance is inversely proportional following a hyperbolic function, while the change in the current strength of a lightning strike is directly proportional to the induced voltage. The induced voltage entering the lightning protection system ranges from 0.041 kV to 2.684 kV. In evaluating the internal protection system, it was concluded that the existing arrester as a protection device was not in accordance with the needs of the protection system, and that the arrester was needed to be replaced because it had reached its working limit. Arresters according to protection system requirements have a test class T2 that is suitable for securing equipment in the system. Then, the grounding system does not comply with PUIL 2011 standards. So it is necessary to design improvements; 10 conductor rods for 4.8Ω ground resistance using a conservative approach. Meanwhile, the BS 7430:2011 standard approach uses 14 conductor rods with a distance of 2 meters for a ground resistance of 4.76Ω or 12 conductor rods with a distance of 3 meters for a ground resistance of 4.97Ω. Keywords: Lightning, Internal Lightning Protection System, Induced Voltage, Arrester, Earth Resistance